2013
DOI: 10.1111/cas.12236
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of CD44v‐xCT system in the development of spasmolytic polypeptide‐expressing metaplasia

Abstract: Cancer development is often preceded by the appearance of preneoplastic lesions. In gastric carcinogenesis, chronic inflammation and histopathologic progression of the stomach epithelium lead to the development of metaplasia and eventually adenocarcinoma. The cell surface protein CD44, especially its variant isoforms (CD44v), has been implicated in metaplasia-carcinoma sequence progression in the stomach. We recently found that CD44v interacts with and stabilizes xCT, a subunit of the cystine transporter syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 34 publications
(79 reference statements)
5
81
0
Order By: Relevance
“…33 CD44v9 staining was found in the basolateral membrane in 32% of cells at the base of the first gland (Fig. 2, Table 2).…”
Section: Resultsmentioning
confidence: 94%
“…33 CD44v9 staining was found in the basolateral membrane in 32% of cells at the base of the first gland (Fig. 2, Table 2).…”
Section: Resultsmentioning
confidence: 94%
“…26,27 Furthermore, CD44v expression was increased in these gastric tumor cells, and inhibition of cystine transport by system xc(−) with sulfasalazine, an inhibitor of xCT-dependent cystine transport, suppressed the development of gastric tumors in these transgenic mice. 28 Our findings revealed that targeted therapy against the CD44v-xCT system may provide a strategy for targeting CSCs in GC treatment. However, a recent study indicated …”
Section: Critical Analysis Of the Potential For Targeting Cscs In Gcmentioning
confidence: 72%
“…Moreover, we found that CD44v expression was upregulated in these gastric tumor cells. We also showed that the inhibition of the cystine transport system xc(-) with sulfasalazine, an inhibitor of xCT-dependent cystine transport, suppressed the progression of gastric tumors in these transgenic mice [55] . Our findings suggest that targeted therapy against the CD44v-xCT system may provide a strategy for the targeting of CD44v positive GCSCs.…”
Section: Current Treatment Of Gc and The Potential For Targeting Gcscsmentioning
confidence: 74%